exam3sampleans

# exam3sampleans - Sample questions for Exam 3 1 Find the...

This preview shows pages 1–4. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Sample questions for Exam 3 1. Find the general solution to y 00- 2 y- 8 y = te 4 t + 3 e t using variation of parameters. Solution: The homogeneous solution is y h = C 1 e 4 t + C 2 e- 2 t . Assume the particular solution has the form y p = u 1 ( t ) e 4 t + u 2 ( t ) e- 2 t where the unknown functions u 1 ( t ) and u 2 ( t ) satisfy u 1 e 4 t + u 2 e- 2 t = 0 u 1 (4 e 4 t ) + u 2 (- 2 e- 2 t ) = te 4 t + 3 e t . Multiplying the first equation by- 4 and adding it to the second equation eliminates u 1 :- 6 u 2 e- 2 t = te 4 t + 3 e t u 2 =- 1 6 te 6 t- 1 2 e 3 t . Multiplying the first equation by 2 and adding it to the second eliminates u 2 : 6 u 1 e 4 t = te 4 t + 3 e t u 1 = t 6 + 1 2 e- 3 t . Integrating, u 1 ( t ) = t 2 12- 1 6 e- 3 t u 2 ( t ) =- 1 36 te 6 t + 1 216 e 6 t- 1 6 e 3 t y p ( t ) = t 2 12- 1 6 e- 3 t e 4 t +- 1 36 te 6 t + 1 216 e 6 t- 1 6 e 3 t e- 2 t = t 2 12- t 36 + 1 216 e 4 t- 1 3 e t . The general solution is y ( t ) = C 1 e 4 t + C 2 e- 2 t + t 2 12- t 36 + 1 216 e 4 t- 1 3 e t . 1 2. Find the solution to y 00 + y- 2 y = 5 e 3 t , y (0) = 1 , y (0) =- 1 using (a) variation of parameters and (b) Laplace transforms. Solution: (a) Variation of parameters: y h = C 1 e t + C 2 e- 2 t y p = u 1 ( t ) e t + u 2 ( t ) e- 2 t u 1 e t + u 2 e- 2 t = 0 u 1 e t- 2 u 2 e- 2 t = 5 e 3 t Solving for u 1 and u 2 , u 1 = 5 3 e 2 t u 2 =- 5 3 e 5 t Then u 1 = 5 6 e 2 t u 2 =- 1 3 e 5 t y p = 5 6 e 3 t- 1 3 e 3 t = 1 2 e 3 t y ( t ) = C 1 e t + C 2 e- 2 t + 1 2 e 3 t . The initial conditions give C 1 + C 2 + 1 2 = 1 and C 1- 2 C 2 + 3 2 =- 1. Therefore C 1 =- 1 2 and C 2 = 1. Therefore y ( t ) =- 1 2 e t + e- 2 t + 1 2 e 3 t . (b) Laplace transforms. s 2 Y- s + 1 + sY- 1- 2 Y = 5 s- 3 Y = s s 2 + s- 2 + 5 ( s- 3)( s 2 + s- 2) = s ( s- 1)( s + 2) + 5 ( s- 3)( s- 1)( s + 2) = 1 3 1 s- 1 + 2 3 1 s + 2 + 1 2 1 s- 3- 5 6 1 s- 1 + 1 3 1 s + 2 Y =- 1 2 1 s- 1 + 1 s + 2 + 1 2 1 s- 3 . y ( t ) =- 1 2 e t + e- 2 t + 1 2 e 3 t . 2 3. Find the general solution to y 00 + 9 y = sec 3 t....
View Full Document

## This note was uploaded on 04/23/2008 for the course MA 232 taught by Professor Toland during the Fall '08 term at Clarkson University .

### Page1 / 11

exam3sampleans - Sample questions for Exam 3 1 Find the...

This preview shows document pages 1 - 4. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online